Market structure and the taxation of international trade - Michael Pflüger; Andreas Haufler (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
The paper compares non-cooperative commodity taxation under the destination and origin principles under a variety of different assumptions about market structure. We consider a model of international duopoly with either quantity or price competition of firms and either segmented or integrated markets, and a monopolistic competition model with mobile firms. In each setting the international spillovers of tax policy are isolated and evaluated at the Pareto efficient tax rate. The sign of the net spillover, and thus the direction that commodity tax com- petition will take, depends critically on whether lump-sum taxes are available or commodity taxes must be used to finance the government budget.
Keywords: H21; F12; H87; 330; tax competition; market imperfections; international trade; Verbrauchsteuer; Steuerwettbewerb; Neue Aussenhandelstheorie; Ursprungslandprinzip; Duopol; Monopolistischer Wettbewerb; Wohlfahrtseffekt; Theorie